Memaknai Wanita Karir Dalam Diri Ibu Tunggal Bekerja - Salsabilla, Faira; Nursanti, Siti; Utamidewi, Wahyu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to understand the experiences and meanings of the career women's role within themselves as single working mothers. Career women who are single mothers face unique challenges in juggling between their professional responsibilities and their role as single parents. This study focuses on their interpretations of this dual role and how it affects their identity as career women and single mothers. The research method used is a qualitative approach with in-depth interviews with a number of single mothers who also work. The collected data were analyzed using an interpretive approach to identify themes and patterns that emerged in their experiences and interpretations. The results of the study indicate that career women as single mothers experience complex struggles in fulfilling this dual role. They try to integrate the roles of being a mother and a worker by finding the right balance between these two responsibilities. Additionally, they also experience additional pressure and stress in facing social expectations that are often unrealistic. Their interpretations of this role are also related to their identity and self-esteem. Some respondents feel proud to fulfill both of these roles, while others feel burdened by the high demands. There are differences in how they integrate the identities of being a career woman and a single mother, with some respondents emphasizing one role more than the other. This research provides deeper insights into the experiences and meanings of career women as single working mothers. The findings of this study can be useful in the development of policies and programs that support women in fulfilling this dual role more effectively. Additionally, this research can serve as a basis for further studies in this domain that can provide more detailed information about the challenges and strategies that can help career women as single working mothers. Keywords: Career women, single mother, dual roles